Latitudinal Gradient of UV Attenuation Along the Highly Transparent Red Sea Basin. (5th June 2019) - Overmans, Sebastian; Agustí, Susana
Abstract: The tropical and subtropical oceans experience intense incident ultraviolet radiation (280–400 nm) while their water columns are thought to be highly transparent. This combination represents a high potential for harmful effects on organisms, yet only few reports on the UV penetration properties of oligotrophic tropical waters exist. Here, we present the pattern of UV attenuation over a wide latitudinal range of the oligotrophic Red Sea. We recorded spectroradiometer profiles of PAR and UV, together with chlorophyll‐ a (Chl‐ a ) and light absorption by chromophoric dissolved organic matter (CDOM) to determine the contribution of phytoplankton and CDOM toward UV attenuation. Transparency to UV exhibited a distinct latitudinal gradient, with the lowest and highest diffuse attenuation coefficients at 313 nm ( K d (313)) of 0.130 m −1 and 0.357 m −1 observed at the northern coast off Duba, and in the south close to the Farasan islands, respectively. Phytoplankton and CDOM both modulated UV attenuation, but CDOM was found to be the key driver despite the lack of riverine inputs. We confirm that ultraviolet radiation can reach deeper into the Red Sea than previously described, which means its potential to act as a stressor and selective driver for Red Sea organisms may have been underestimated to date. Abstract : The optical properties of the oligotrophic and highly transparent Red Sea represented by the downwelling diffuse attenuation coefficients ( K d ) for the integrated PAR (400–700 nm), UV‐A (320–400 nm) and UV‐B spectra (280–320 nm). PAR and UV‐B were measured during four Red Sea cruises between October 2016 and March 2018, while the UV‐A properties were determined as part of two cruises in August 2017 and March 2018.